P-235 Transforming palliative care education to improve end of life experiences for patients and families in all care settings. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Gordon, Simon
Abstract : Background: A hospice has embarked on an exciting project with Macmillan Cancer Support, the overall aim being to improve palliative care education across the North East. This work follows on from The 'More Care Less Pathway' review in July 2013, which concluded that professionals working with patients and families at the end of life require better training both at induction and throughout the course of their employment, for the benefit of the local community. The Hospice has been successful in receiving funding from Macmillan Cancer Support to begin the research working towards a 'North East Centre for Palliative Care Education'. They will be working in partnership with eight of the region's nine other independent hospices to create a more joined up approach to palliative care education. Aim: The project aims to undertake the crucial ground work required to transform hospice education across the North East. The aim of the project is to reduce duplication and maximise delivery of the hospices education syllabuses to bring the best educationalists from all the region's hospices together, as currently the region does not allow formal and easy sharing of knowledge and expertise. Working as a team, they will eventually provide appropriate and targeted palliative care education for clinicians, care staff and wider hospice functions across the North East from one syllabus to help underpin all hospice delivery. Method: The hospice will first lead on assessing the education needs of the local hospices and their current delivery. Macmillan Cancer Support has funded three crucial posts to enable the hospice to undertake this initial research. This is anticipated to be phase one of a three step process. During phase one: the current collective syllabus will be mapped out using a standard reporting tool to collate all hospice education activity, highlight any gaps against national best practice and identify areas of current strength. At the same time conversations will continue with all education providers across the education sector as to the feasibility of joining up all education in a collaborative setting. Following this, information will be collated and a business case of options for hospice education will be put forward underpinned by support from Deloitte. Conclusion: The evaluation of this work will be ongoing and can be measured in simple terms by the degree of collaboration and output against the project aims.